Sociología del 13, rue del Percebe - Véliz, Sergio B. (Nómadas. Critical Journal of Social and Juridical Science, 2009)
This article aims to make a sociological and semiotic study on the cómic 13, rue del Percebe, of Francisco Ibáñez, tale of great success in Spain during the sixties, the seventies and part of the eighties of the 20th century. In these pages will be analyzed the intimate connection of this comic with social aspects of that historical period and with the topic of the “Picaresque” one. Finally, we will attend to certain formal relations between the language of the cómic in general and the language of 13, rue, in particular.
Keywords: Anarchy; Community (Gemeinschaft) and Association (Gesellschaft); Escopophilia; Voyeurism; Picaresque; No-sequential cómic